A bi-functional alginate-based composite for catalyzing one-pot methyl esters synthesis from waste cooking oil having high acidity. (15th December 2021) - Al-Sakkari, Eslam G.; Attia, Nahed K.; Habashy, Mahmoud M.; Abdeldayem, Omar M.; Mostafa, Salwa R.; El-Sheltawy, Shakinaz T.; Abadir, Magdi F.; Mostafa, Mohamed K.; Rene, Eldon R.; Elnashaie, Said S.E.H.
Graphical abstract: Highlights: Ecofriendly natural materials are transformed to bifunctional solid catalyst. Highly acidic waste cooking oil was converted to biodiesel at a yield of 97%. Developed composite catalyzes simultaneous esterification-transesterification. Full Factorial Design was efficient for optimizing catalyst preparation (error < 4%). The optimum catalyst is stable, not leachable and can be reused up to 25 times. Abstract: A bi-functional catalyst based on natural components was designed and optimized via full factorial design for catalyzing the simultaneous esterification-transesterification process. The factors affecting the catalyst synthesis were as follows: crosslinking time (0.5–2 h), CaCl2 concentration (1–5 w/v%), sodium alginate to k-carrageenan mass ratio (1.5:1–3:1 w/w), and sodium bentonite to k-carrageenan mass ratio (1:1–4:1 w/w). The free fatty acids conversion into esters and total esters yield were the indicative responses. The results from this study showed that the maximum total esters yield of 97% was obtained at a crosslinking time of 0.5 h, CaCl2 concentration of 1 w/v%, sodium alginate to k-carrageenan mass ratio of 1.5:1, and sodium bentonite to k-carrageenan mass ratio of 4:1. The reaction conditions were 21:1 methanol to oil molar ratio, 3 wt% catalyst loading, and 10 min sonication time using a 750 W rod-sonicator. The impulse ratio was 45:30, and the sonication amplitude was 50%. This catalyst was reused 25 times, in some cases, without a decline in its catalytic activity. Furthermore, the catalyst does not leach or dissolve in the reaction medium and the physical characteristics of the methyl esters matched the ASTM standards for biodiesel.